Mobilität und Transport 2025+. - (:unkn) unknown (My University, 2013)
Der Verkehr steht vor dem größten Umbruch seit Beginn der Massenmotorisierung. Durch Megatrends wie Urbanisierung, Digitalisierung und demografischer Wandel verlagert sich der Verkehr stärker vom Auto auf öffentliche Verkehrsmittel sowie Gehen und Radfahren. Um die langfristigen EU-Klimaziele zu erreichen, sind die mit dem Auto in Österreich gefahrenen Kilometer bis zum Jahr 2030 um ein Drittel zu verringern. Wie sieht die Mobilität im Jahr 2025 und danach aus? Die Antworten darauf beeinflussen unseren Wohlstand, unsere Gesundheit und Lebensqualität und entscheiden über die Attraktivität des Wirtschaftsstandorts Österreich. Die Energie- und Klimaziele geben die Richtung vor, die gesellschaftlichen Megatrends beeinflussen die zukünftige Mobilität. Und Rahmenbedingungen wie steigende Energiepreise, knapper werdender Platz in den Städten und Budgetknappheit der öffentlichen Hand erfordern eine höhere Effizienz des Verkehrs.

Basic traffic development targets and their implementation, together with the evaluation of all the traffic development targets and a review of the entire transport system should be combined in the strategy plan "Mobility and Transport", for which the Federal Ministry of Transport, Building and Urban Development holds responsibility. Covering both passenger and freight transport, the plan deals with transport infrastructure, fixtures for transport facilities, operational and legal systems, organization, and responsibilities of concerned authorities, information systems, and other relevant basic conditions. The starting point for strategic planning, which is focused on target-orientation and work-related guidance, covers the targets or target-settings for the development of an overall transport system. Due attention is given to the feasibility of target achievement, the economical use of the financial means available to cover the construction, expansion, renovation, maintenance and functional aspects of transport infrastructure, transport safety by taking into account the targets and task-settings ahead, climatic protection and a reduction of climate-relevant emissions (CO2), the reduction in environmental pollution caused by transport-generated noise and air pollutants, the economical use of existing space, also for future sustainable development.
Strategic planning for mobility and transport.
Keywords: Verkehr; Verkehrspolitik; Mobilität; Transport; Verkehrsmittelwahl; Verkehrsinfrastruktur; Verkehrsentwicklung; Entwicklungstendenz; Nachhaltige Mobilität